Towards Ethical Data Ecosystems: A Literature Study - Minna M. Rantanen; Sami Hyrynsalmi; Sonja M. Hyrynsalmi (United States, 2022)
While the importance of data is growing as the fuel
of the new data economy, also the role of the data ecosystems
is growing. The new data ecosystems enables the use, reuse and
enrichment of big data sets by or together with third parties.
However, in the context of technology management, the governance
of these kinds of data ecosystems raises ethical questions
and issues that should be acknowledged by researchers and
practitioners. This study reviews the extant literature regarding
the given advice about ethical considerations. The method of
systematic literature study is used to collect the primary articles
(N=20). The selected articles are analyzed and themed according
to reoccurring themes: privacy, accountability, ownership,
accessibility, and motivation. The results show the discussion is
fragmented and concrete ethical guidelines are lacking. Thus,
this study requires more work for governing data ecosystems in
an ethical way.
2019 IEEE International Conference on Engineering, Technology and Innovation (ICE/ITMC)